Peter Brears: Traditional Food in Northumbria - Clark, Letitia (Petits Propos Culinaires, 2013)
Peter Brears: Traditional Food in Northumbria: Excellent Press, Ludlow, 2013: 285 pp., illustrations, hardback, £19.99.